Diversity in the traditional fermented foods of Malaysia and their potential as probiotic source - Siti Maryam, Ahmad Rumaizi; Shariza, Jamek; Norazsida, Ramli; Nik Raihan, Nik Him; Mohd Shafiq, Mohd Sueb; Zatul Iffah, Mohd Arshad (Malaysian Society For Biochemistry & Molecular Biology (MSBMB), 2022)
Fermentation is one of the oldest methods of food preservation. Over the centuries, it has evolved, improved, and diversified. The microbial population, an important component of fermented foods, aids in the preservation of nutrients and extends the shelf life of food. These microbes have attracted further interest due to their genetic similarity to probiotic strains. Probiotics are live microorganisms that, when consumed in sufficient numbers, promote the host's health. Although lactic acid bacteria (LAB) from various genera, such as Lactobacillus, Streptococcus, and Leuconostoc, are the most prevalent in fermented foods, other bacteria, yeast, and fungi also contribute to food fermentations. Local diets have traditionally featured a range of indigenous fermented foods containing probiotic microorganisms. Besides, there is growing interest in commercialising Malaysian-traditional fermented foods as natural prebiotic foods rich in health-promoting bacteria. Probiotic products, such as fermented foods, are becoming more popular due to their health benefits and consumer accessibility. This article aims to provide an overview of recent studies on the potential source of probiotics from Malaysian traditional fermented foods to understand their importance in healthy diets better.